The Role of Reconciliation Theology in Socio-Political Healing and Development - Isiaho, Muhati Allan (Evangelical review of theology, 2020)
The article discusses the role of theology in international peace and socio-political healing and mentions people who are affected by large-scale criminal violence. Topics discussed include inability of social institutions in delivering essential services to the citizens, long-standing issues which affect sustainable peace, and restoration of socio spiritual harmony.